Formulating SLN and NLC as innovative drug delivery systems for non-invasive routes of drug administration - Fonseca-Santos, Bruno [UNESP]; Silva, Patrícia Bento; Rigon, Roberta Balasin; Sato, Mariana Rillo [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2020)
Colloidal carriers diverge depending on their composition, ability to incorporate drugs and applicability, but the common feature is the small average particle size. Among the carriers with the potential nanostructured drug delivery application there are SLN and NLC. These nanostructured systems consist of complex lipids and highly purified mixtures of glycerides having varying particle size. Also, these systems have shown physical stability, protection capacity of unstable drugs, release control ability, excellent tolerability, possibility of vectorization, and no reported production problems related to large-scale. Several production procedures can be applied to achieve high asso-ciation efficiency between the bioactive and the carrier, depending on the physicochemical properties of both, as well as on the production procedure applied. The whole set of unique advantages such as enhanced drug loading capacity, prevention of drug expulsion, leads to more flexibility for modulation of drug release and makes Lipid-based nanocarriers (LNCs) versatile delivery system for various routes of administration. The route of administration has a significant impact on the therapeutic outcome of a drug. Thus, the non-invasive routes, which were of minor importance as parts of drug delivery in the past, have assumed added importance drugs, proteins, peptides and biopharmaceuticals drug delivery and these include nasal, buccal, vaginal and transdermal routes. The objective of this paper is to present the state of the art concerning the application of the lipid nanocarriers designated for non-invasive routes of administration. In this manner, this review pre-sents an innovative technological platform to develop nanostructured delivery systems with great versatility of application in non-invasive routes of administration and targeting drug release.
Keywords: Colloidal carriers; Lipid-based nanocarriers (LNCs); Nanostructured lipid carriers (NLC); Nanostructured systems; Non-invasive routes of administration; Solid lipid nanoparticles (SLN)